Pengaruh Temperatur Udara, Kelembaban Udara, Kecepatan Udara dan Intensitas Cahaya terhadap Daya Listrik Panel Surya - Johan, Henny; Utomo, Niko; Wardana, Rendy Wikrama (EduFisika: Jurnal Pendidikan Fisika, 2022)
This study aims to analyze the effect of temperature, humidity, air speed and sunlight intensity on the electricity generated by solar panels. The research method used is the experimental method, by collecting data directly using two solar panels arranged in series and parallel and carried out in two different places, namely the coastal area and the highlands. The results showed that the temperature, humidity and air velocity with tcount were -0.5765; 0.0063; and 0.5608. The value of tcount is smaller than ttable 2.2281 indicating there is no significant effect between temperature, humidity and air velocity on solar panel electric power. For light intensity, the tcount value is 2.301. The value of tcount is greater than ttable 2.2281, so it can be concluded that there is a significant effect between light intensity and solar panel electric power.